Changes of Local to Global Organizations at Pos Keadilan Peduli Ummat Human Initiative - Eriman Muslim; Sari Viciawati Machdum (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study discusses the practice of changing local organizations to become global at Pos Keadilan Peduli Ummat Human Initiative, which is located in Depok, West Java. Contingency theory is used as the basis for research, where the organization is an open system whose internal structure adapts to changes in the external environment and technology so that its effectiveness can continue to be sustainable. This research uses a qualitative approach with descriptive research——informant selection technique in this study, using purposive sampling. The data collection used in-depth interviews with several informants consisting of the founders of the organization, the structural ranks of the board of directors at the time of the research, senior workers and retired workers. The study results indicate that changing local organizations to global ones from the Justice Center Peduli Ummat Human Initiative occurs due to adjusting the internal structure to the demands of changes in the external environment and technology. The dynamics of the leadership dynamics evidence. This change in evidence ranks at the director's level and below him, the use of technology and information under the times and the strengthening of the capacity of its human resources. The need to change turned out to cause internal impacts such as egalitarian attitudes to become formal, the inconvenience of old workers and the need to be technology literate.